Antagonism of tone and prostaglandin-mediated responses in a tracheal preparation by indomethacin and SC-19220 - Farmer, J.B. (1974)
1 The effects of the prostaglandin synthetase inhibitor, indomethacin and the prostaglandin antagonist SC-19220 (1-acetyl-2-[8-chloro-10,11-dihydrodibenz (b,f) (1,4)oxazepine-10-carbonyl] hydrazine), were examined on the tone of the guinea-pig isolated tracheal preparation and on the responses of the preparation to prostaglandin F(2α), arachidonic acid and methacholine. 2 Indomethacin (0.05-1.6 μg/ml) produced a long-lasting inhibition of the intrinsic tone of the tracheal preparation and of the contractile responses to arachidonic acid. Much higher concentrations of indomethacin also reduced the responses of the preparation to methacholine. This effect was readily reversible and appeared to be unrelated to the action on tone. 3 The contractile responses of the preparation to prostaglandin F(2α) were enhanced by low concentrations of indomethacin (1-5 μg/ml) and inhibited by higher concentrations (2.5-80 μg/ml). 4 SC-19220 was shown to inhibit responses of the preparation to prostaglandin F(2α) in concentrations (0.1-1 μg/ml) which had no effect on responses to methacholine. Similar concentrations also inhibited the intrinsic tone of the preparation and the responses to arachidonic acid. 5 The evidence suggests that prostaglandins may be involved in the maintenance of tone of the guinea-pig isolated tracheal preparation.